2012
DOI: 10.1073/pnas.1119238109
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's tyrosine kinase phosphorylates Toll-like receptor 3 to initiate antiviral response

Abstract: Toll-like receptor 3 (TLR3) mediates antiviral response by recognizing double-stranded RNA. Its cytoplasmic domain is tyrosine phosphorylated upon ligand binding and initiates downstream signaling via the adapter TIR-containing adaptor inducing interferon-β (TRIF). However, the kinase responsible for TLR3 phosphorylation remains unknown. We show here that Bruton's tyrosine kinase (BTK)-deficient macrophages failed to secrete inflammatory cytokines and IFN-β upon TLR3 stimulation and were impaired in clearing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
120
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 43 publications
1
120
0
1
Order By: Relevance
“…To understand further the mechanism by which the activation of TLR signaling in macrophages promoted tumor cell phagocytosis, we treated macrophages by combining TLR agonists with various inhibitors targeting key molecules that positively (MAPK, Btk) (23)(24)(25)(26)(27) or negatively (PI3K, caspase-1) (28,29) regulate TLR signaling. Blockers of MAPK, PI3K, and caspase-1 showed no effect on phagocytosis of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…To understand further the mechanism by which the activation of TLR signaling in macrophages promoted tumor cell phagocytosis, we treated macrophages by combining TLR agonists with various inhibitors targeting key molecules that positively (MAPK, Btk) (23)(24)(25)(26)(27) or negatively (PI3K, caspase-1) (28,29) regulate TLR signaling. Blockers of MAPK, PI3K, and caspase-1 showed no effect on phagocytosis of cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the implication of EGF receptor-recruited Src in TLR3 Tyr-759 phosphorylation has been shown in constitutive Src-expressing cells (29), supporting the importance of Src in TLR3-induced signaling as we reported in this study. Recently, the role of BTK has been implicated in TLR3 Tyr-759 phosphorylation and initiating antiviral responses in dsRNA-treated macrophages (28). Given that BTK was activated within 30 min after dsRNA stimulation, BTK might be the kinase responsible for the early TLR3 Tyr-759 phosphorylation in macrophages.…”
Section: Inos/src/tlr3 Axis In Tlr-mediated Ifn-␤ Productionmentioning
confidence: 99%
“…signaling (18,26,28), the essential role of iNOS and Src in dsRNA-mediated TLR3 Tyr-759 phosphorylation and IFN-␤ production has not been investigated in the past. In this study, we demonstrated that dsRNA-stimulation induced a biphasic (early versus late) TLR3 Tyr-759 phosphorylation in macrophages.…”
Section: Inos/src/tlr3 Axis In Tlr-mediated Ifn-␤ Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, however, have focused on its role in regulating innate immune responses in myeloid cells, acting downstream of TLR4 and the antiviral TLRs, TLR3, -7, and -9, to regulate proinflammatory cytokine and type I IFN production (6)(7)(8)(9)(10)(11). Btk has also been shown to interact with and become activated following ligation of TLR8 and -9 in the monocytic cell line THP-1 (8).…”
mentioning
confidence: 99%